Dragon, Chameleon or Chinese Mosaic? Tomasz Ewertowski Images of China in Polish and Serbian Travel Writings (1720–1949), Brill Rodopi, Leiden – Boston 2020. - Sylwia Nowak-Bajcar, (Porównania, 2024)
This article is a review of Tomasz Ewertowski’s book from 2020, which is an innovative publication in the field of Slavic studies both in terms of the choice of topic, its comparative approach and the method of analysis and interpretation of sources. So far, there has not been an equally extensive, comprehensive, exhaustive (though not closed), systematizing discussion of the issue announced in the title, a discussion that would present such an in-depth analysis of meticulously collected sources, including archival materials, so far unpublished. The author of the publication comes to the conclusion that it is impossible to create a common, generalized image of China that would emerge from these analyses, or to create certain fixed rules that clearly define the impact of biography, the nature of travel and political factors on the image of this country. Therefore, the monograph does not provide a clear answer to the question of what China is, let alone what it is like. Let us add, however, that this was not the goal and intention of the author, who in the conclusion of his book proposed that the Chinese unity in the multiplicity of representations should be defined by the mosaic metaphor he aptly indicated.